2004
DOI: 10.1063/1.1796232
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric study of the α and β processes in supercooled ethylene glycol oligomer–water mixtures

Abstract: Broadband dielectric measurements for 65 wt % ethylene glycol oligomer (EGO)-water mixtures with one to six repeat units of EGO molecules were performed in the frequency range of 10 microHz-10 GHz and the temperature range of 128-298 K. In the case of the water-EGO mixtures with one and two repeat units of the EGO molecule (small EGO), the shape of the dielectric loss peak of the primary process is asymmetrical about the logarithm of the frequency of maximum loss above the crossover temperature, T(C). The asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 52 publications
3
90
0
Order By: Relevance
“…Moreover, the different temperature dependences of the relaxation time of process-II at temperatures above and below the T g of arabinose-water binary systems are more or less the same as the relaxation times observed in various aqueous solutions. [7][8][9][10][11][14][15][16][17][18][19][20][21][22] These similar properties suggest that the relaxation process-II observed in d-arabinose-water systems is due to the reorientational motion of water in these mixtures. Recently, Kaminski et al [29] have shown that pure d-arabinose possesses two kinds of relaxation processes, namely a and g. For each water concentration, the relaxation time of process-II is closer to the g-process of anhydrous d-arabinose (Figure 6 b), but the interesting point is that their dielectric strengths have much higher magnitudes as compared to the g-process of darabinose.…”
Section: Secondary or Process-ii Relaxationmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the different temperature dependences of the relaxation time of process-II at temperatures above and below the T g of arabinose-water binary systems are more or less the same as the relaxation times observed in various aqueous solutions. [7][8][9][10][11][14][15][16][17][18][19][20][21][22] These similar properties suggest that the relaxation process-II observed in d-arabinose-water systems is due to the reorientational motion of water in these mixtures. Recently, Kaminski et al [29] have shown that pure d-arabinose possesses two kinds of relaxation processes, namely a and g. For each water concentration, the relaxation time of process-II is closer to the g-process of anhydrous d-arabinose (Figure 6 b), but the interesting point is that their dielectric strengths have much higher magnitudes as compared to the g-process of darabinose.…”
Section: Secondary or Process-ii Relaxationmentioning
confidence: 82%
“…Thus, much attention has been paid in the literature to the dielectric behavior of water dynamics in several aqueous mixtures, such as carbohydrates, [7][8][9][10][11] proteins, [12,13] and polymers. [14][15][16][17][18][19][20] Among the various glass-forming materials, the study of the dynamical behavior of carbohydrates (mono-, di-, and polysaccharides) possesses an essential interest, as they belong to an interesting group of materials able to undergo a glass transition both in the anhydrous form and in aqueous solutions. Although an enormous amount of work has been devoted to the understanding of its occurrence in supercooled systems, many unresolved issues [21] are still left to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In solutions containing solutes with a low molecular weight, such as alcohols (molecular weight, M W 100), the observed relaxation curve was asymmetric with respect to the loss peak above the separation temperature T S [39,40,55,[59][60][61], as shown in Fig. 9.3a.…”
Section: Glass Transition In Water-containing Systemsmentioning
confidence: 89%
“…Here, we call it ν-relaxation [55], ν being the initial letter of νερo, which means water in Greek. It was shown that ν-relaxation is the primary dielectric relaxation of water observed in various aqueous solutions at around room temperature, and the shape of the ν-relaxation spectrum depends on the molecular weight of the solute [39,40,55,[58][59][60][61][62].…”
Section: Glass Transition In Water-containing Systemsmentioning
confidence: 99%
See 1 more Smart Citation